Prepping and shooting your student short film a brief guide to film production - Kelly, Rory (Routledge, Taylor & Francis Group, 2023)
"Focusing on the practical tools required to making your first student film, this book is a concise and accessible guide to film production. Demystifying the process of taking a film from concept through to production, author Rory Kelly covers all the key bases including: organizing your script, when and how to shoot, production budgeting, finding actors and locations, and roadmapping postproduction. Featuring common problems and challenges producers and directors face throughout the production process and providing practical solutions, the book illustrates how to effectively create a film that can be successfully shot in a classroom or micro-budget environment. Filmmakers will be empowered to prioritize realistic goals, balance practical and creative demands, manage a budget, and schedule time to ensure concept translates to reality. Kelly brings together the creative process and practicalities of producing a student film. A concise and accessible guide written with the specific constraints of a student production in mind, this book will equip any filmmaker with the tools to produce an impactful short film. Ideal for undergraduate and graduate students of filmmaking, amateur filmmakers, as well as students in high school, community-based, for-profit and summer filmmaking programs. Additional downloadable online resources include a look-book with images and video clips, as well as printable budget templates, shooting schedule templates, block breakdown sheets, a digital workflow worksheet, timed shot-list forms and templates for location agreements, appearance releases, crew deal memos and call sheets"--